Islamic Slang: Shaping the Communication Style and Religious Identity of Gen Z Students - Nur Aziza Labalo Aziza; Nopa Samdin; Siti Selviah; Risaldi Firmansya mukhtar (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
This study examines the use of Islamic slang as a communication style and its role in shaping the religious identity of Generation Z students in school environments. The research aims to analyze how Islamic slang is used in students' daily interactions, its contribution to the construction of religious identity, its influence on communication patterns among students, and its role in strengthening religious character and conveying Islamic values. This study employed a qualitative library research approach by reviewing books, journal articles, and other relevant scholarly sources related to sociolinguistics, Islamic communication, and youth language. The collected data were analyzed descriptively through data reduction, categorization, interpretation, and synthesis. The findings indicate that Islamic slang functions not only as a form of informal communication but also as a symbolic expression of students' religious identity. The use of expressions such as mā shāʾ Allāh, astaghfirullāh, barakallāh, akhi, and ukhti contributes to strengthening interpersonal relationships, fostering a sense of belonging among peers, and supporting the internalization of Islamic values in everyday communication. Furthermore, Islamic slang reflects an adaptive strategy for contemporary da'wah that aligns with the characteristics of Generation Z. However, its use requires appropriate guidance to preserve the sacred meanings of religious expressions and ensure their contextual and ethical application in educational settings